An Ultrastable Low-Temperature Na Metal Battery Enabled by Synergy between Weakly Solvating Solvents - Wang, Shuzhan; Zhang, Xia-Guang; Gu, Yu; Tang, Shuai; Fu, Yongzhu (Journal of the American Chemical Society, 2024)
The low ionic conductivity and high desolvation barrier are the main challenges for organic electrolytes in rechargeable metal batteries, especially at low temperatures. The general strategy is to couple strong-solvation and weak-solvation solvents to give balanced physicochemical properties. However, the two challenges described above cannot be overcome at the same time. Herein, we combine two different kinds of weakly solvating solvents with a very low desolvation energy. Interestingly, the synergy between the weak-solvation solvents can break the locally ordered structure at a low temperature to enable higher ionic conductivity compared to those with individual solvents. Thus, facile desolvation and high ionic conductivity are achieved simultaneously, significantly improving the reversibility of electrode reactions at low temperatures. The Na metal anode can be stably cycled at 2 mA cm–2 at −40 °C for 1000 h. The Na||Na3V2(PO4)3 cell shows the reversible capacity of 64 mAh g–1 at 0.3 C after 300 cycles at −40 °C, and the capacity retention is 86%. This strategy is applicable to other sets of weak-solvation solvents, providing guidance for the development of electrolytes for low-temperature rechargeable metal batteries.